IMPLICATIONS OF ZONATION SYSTEM AND EFFORTS TO OVERCOME STUDENTS LEARNING DIFFICULTIES - Enung Nugraha; Muhamad Fauzi; Yani Susilo Hesti (STAI Hubbulwathan Duri, 2020)
This study aims to determine the zoning system's application for the admission of new students and determine the efforts of schools and teachers to overcome learning difficulties as a negative impact of the application of the zoning system. The research method used is descriptive qualitative with a phenomenological approach. The research object was in the Junior High Schools 1, 5, and 10 Serang City, while the data obtained through interviews with the principal and vice-principal of the school. The results showed that the zoning system's implementation for new students' admission was following government policy. The efforts schools and teachers' to helping student learning difficulties by adding learning hours for students who experience learning difficulties at schools on health protocols as part of the 'new normal' through a scheduled and limited system, the importance of parental participation in coaching and supervision of learning at home and assist their friends or seniors to understand the substance earlier learning.